Notes on food of Capricornis milneedwardsii in the Cat Ba archipelago, Hai Phong, Vietnam - Thuc, Phan Duy; Hieu, Dao Ngoc; Thap, Hoang Van; Van, Vu Hong; Khu, Nguyen Xuan (Academia Journal of Biology, 2013)
The Southwest China serow, Capricornis milneedwardsii, is widespread through Myanmar, Cambodia, northern Thailand, Laos, central and southwest China, and Vietnam. However, this species is listed as Near Threatened in IUCN Red List and its ecology, especially the diet of this species is poorly understood. The data of food plants of the Serow in Cat Ba Archipelago was taken by interviewing the Cat Ba National Park’s rangers and members of forest protection groups on the feeding sites of the species, and then conducting field surveys. The results of interviews were carefully crosschecked in the field to determine the food plants of the Serow in the Cat Ba Archipelago. The species’ food plants were collected in the browsing zone up to 1.5m above ground and uneaten parts of less than 5mm in diameter. The study found that at least 33 different plant species of 22 families was determined as food plants of the serow in the archipelago. These plants were mostly found in secondary evergreen moist forests on limestone, accounting for 71%, and most of the species’ food plants are shrubs, accounting for 73%. The serows also feed mainly on the leaves and twigs of shrubs and low growing trees and thus the Southwest China serow is categorized as a typical browser. Most of the plant species consumed by the serows have utility as medicinal herbs and edible sources for humans and thus they are being massively exploited by local people. This may have an impact on the population viability of the Southwest China serow in the Cat Ba Archipelago.